Pemanfaatan Minyak Atsiri Kulit Jeruk Bali (Citrus maxima) Sebagai Alternatif Antibakteri Staphylococcus epidermidis dan Staphylococcus aureus Pada Deodoran spray - Octaviani, Dilha; Farid, Nurfiddin; Syarifuddin, Surya (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Cleanliness and body odor are major and important factors of personal hygiene and appearance. If a person's body smells good, their self-confidence will be higher. Using soap and water as a body wash when bathing is relatively ineffective in preventing body odor. So several other alternative actions can be taken, such as using anti-body odor cosmetic preparations (deodorant). This research aims to determine whether grapefruit peel (Citrus maxima) essential oil can be formulated as a spray deodorant that meets physical quality requirements and to determine its antibacterial effectiveness on Staphylococcus epidermidis and Staphylococcus aureus. The method used in this research is experimental with a formula design divided into four formulas, F0 without essential oil, F1 with the addition of 0.5% essential oil, F2 with the addition of 1% essential oil, and F3 with the addition of 1.5% essential oil. The finished doedorant preparation was then subjected to organoleptic testing, homogeneity, pH, dry time, spraying pattern, cycling test for 6 cycles, and antibacterial activity test. The results of this research show that grapefruit peel (Citrus maxima) essential oil can be made into a spray deodorant that meets physical quality requirements. The results of the research show that the formulation has antibacterial activity against Staphylococcus aureus bacteria, with an F1 inhibition zone of 0.5% 3.8 mm (weak), F2 1% 4.5 mm (weak), F3 1.5% 15.2mm (strong). In Staphylococcus epidermidis bacteria, the inhibition zone is F1 0.5% 3.5 mm (weak), F2 1% 4.6 mm (weak), and F3 1.5% 14.8 mm (strong).